2016
DOI: 10.1007/978-3-319-27349-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine-Based Definitions: From Baseline Creatinine to Serum Creatinine Adjustment in Intensive Care

Abstract: This article is one of ten reviews selected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…In the critically ill, several confounders affecting Cr‐based AKI definitions have been identified. These include volume overload and subsequent dilution of Cr, malnutrition, and muscle wasting . We did not find difference in cumulative fluid balances among patients with and without AKI in the first 6 hours, and thus, the Cr P value is unlikely to be affected by fluid balance .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In the critically ill, several confounders affecting Cr‐based AKI definitions have been identified. These include volume overload and subsequent dilution of Cr, malnutrition, and muscle wasting . We did not find difference in cumulative fluid balances among patients with and without AKI in the first 6 hours, and thus, the Cr P value is unlikely to be affected by fluid balance .…”
Section: Discussionmentioning
confidence: 52%
“…The primary outcome was AKI on day 2 based on Cr DAY2 measurement and determined according to the Kidney Disease: Improving Global Outcomes (KDIGO) Cr and RRT criteria . Cr F served as the baseline Cr as no data regarding outpatient Cr values preceding the index hospitalization were available. Data about urine output normalized to patient weight were unavailable which prevented the application of the KDIGO urine output criteria for AKI.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we found that combination with biomarker NephroCheck and risk factors for risk assessment of AKI has the greatest signi cance to patients with uncertain disease trajectories. Future research needs to clinically or electronically identify patients at high risk of AKI development or progression to CKD or ESRD [1,33]. We plan to develop an electronic alert system including the assessment of NephroCheck and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…AKI was diagnosed as determined by an adjudication committee of 3 expert nephrologists who were blinded to the biomarker results, based on the KDIGO criteria (5) using the peak postoperative sCr within 10 days after surgery and excluding sCr at admission to postoperative ICU. Baseline sCr was defined as the usual value of sCr preceding the admission within at least 7 days (12) or as the nadir sCr after recovery of renal function (13).…”
Section: Methodsmentioning
confidence: 99%